IDENTIFIKASI SENYAWA TANIN PADA DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Yusi Hidjrawan (Jurnal Optimalisasi, 2018)
This study aims to identify tannin compounds in the leaves of starfruit (Averrhoa bilimbi L.) and to find out the benefits of starfruit leaves. starfruit leaf extract obtained through starfruit leaves crushed first, then added a solution of methanol and then filtered using filter paper, then extracts of starfruit leaf extract divided into two test tubes, in which one tube is dripped with iron (III) chloride. The results showed that, the color of the wuluh starfruit leaf extract which was originally brownish yellow turned blackish blue. It can be concluded that the starfruit leaves of tannin compounds were identified. Tannin compounds function to bind and precipitate protein. So that in health tannins function to treat diarrhea, treat hemorrhoid, stop inflammation and also can be a natural alternative to cleaning artificial teeth.